Optimization Methods in Physical Education Lessons for Girls in the Second and the Third Grades - Almagul Ilyasova; Valery Kovalenko; Zhanymmurat Erzhanov (Lithuanian Sports University, 2018)
Background. Theoretical analysis of research papers allowed us to establish that physical preparation of pu- pils in elementary grades as an area of scientific and pedagogical knowledge was not investigated enough. Despite great efforts to cover a lot of questions and undoubted theoretical and practical significance of educational research, it should be noted that the problem of physical education for younger pupils using sports games in the lessons of physical education remains open to theoretical understanding and experimental study. There is a lack of specific studies that reveal the basic trends and ways to optimize the studied phenomenon. Worsening situation in the area of physical training in junior classes and individual indicators of health status in the country encourages looking for scientific solutions of the problem. Research aim was to define the most effective methods of physical education for 8-9-year-old girls, learners of the second and third grades, during physical education lessons including elements of sports games in a comprehensive school. Methods. Research participants were 64 girls from the second and the third grades. They were divided into 4 groups - 3 experimental groups and one control group. During the experiment, group E1 was allotted 75% of the time of the lesson for training technical actions of sports, group E2 - 50% in E3 - 25%, for the development of physi- cal skills - 25, 50 and 75% respectively. The effectiveness of the proposed program was estimated by the changes in the indicators of physical development and general physical fitness. Results and conclusions. Physical development of girls during the school year changed considerably. The most clearly expressed change was noted in the results of the changes in the girls' body weight, from 20.32 to 23.24% in all groups. No significant differences between the experimental and control groups in terms of physical development were identified. Indicators of general physical fitness for the whole period of the experiment significantly increased in all the groups studied (p < .05-.001). They may be divided into two groups: •  The first group included indicators which were significantly higher in the experimental group E3, where more time was devoted to physical training (running at 30 m, the hand strength) during the physical educa- tion lessons; •  The second group included indicators which were significantly higher in the experimental group E1, where more time was devoted to sports (long jump, making a shot, running 3 x 10 m) during physical education lessons. Thus,  the  lessons  of  physical  education  with  elements  of  sports  promoted  more  intensive  development  of the overall fitness of girls aged 8-9 years compared to those who attended physical education lessons conducted according to the general curriculum. Keywords: girls in the second and the third grades, physical education class, physical development, physical ftness, sports and games.